Outcomes of implantation of modified capsule tension rings with multiple black occluder paddles for eyes with congenital and acquired iris defects: Report 3. Issue 6 (June 2016) - Miller, Kevin M.; Nicoli, Manuel C.; Olson, Michael D.; Shah, Manali; Masket, Samuel
Abstract : Purpose : To evaluate the safety and efficacy of Morcher 50F iris diaphragm implantation to manage moderate to large defects of the human iris. Setting : Stein Eye Institute, UCLA, Los Angeles, California, USA. Design : Prospective nonrandomized interventional case series. Methods : The demographic, preoperative, and postoperative data of patients who had implantation of modified capsular tension rings and followed to 1 year were reviewed. Safety measures included loss of corrected distance visual acuity (CDVA), surgical complications, adverse events, and secondary surgical interventions. Efficacy measures included CDVA with glare, daytime and nighttime glare symptom scores, and subjective cosmesis scores. Results : The study comprised 12 patients. The median CDVA was 20/70 before surgery and 20/20 after surgery. There were no lost lines of CDVA and no intraoperative complications. The most common postoperative complication was posterior capsule opacification. Two adverse events were unrelated to the device. Four patients had secondary surgical interventions, the most common of which was laser capsulotomy. The median CDVA with glare improved from less than 20/400 before surgery to 20/50 after surgery. One patient worsened. The median subjective daytime glare symptom score improved from 9 to 3 on a 10‐point scale ( P = .001). The median nighttime subjective glare symptom score improved from 8 to 2 ( P = .001). The subjective cosmetic appearance of the eye stayed the same or improved for all patients ( P = .031). Conclusion : Iris diaphragm implantation was relatively safe and effective for reducing light and glare sensitivity in eyes with iris defects when combined with cataract extraction and intraocular lens implantation. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.